Proportional Resonance and Fractionalorder Proportional Integral Derivativebased Closed-loop Drug Infusion for the Regulation of Mean Arterial Pressure in Critical Care Patients – A Modeling and Simulation Study - Chandramouli, R. (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: Managing hypertensive emergencies are a common occurrence in critical care setups. Mean arterial pressure (MAP) is an important hemodynamic variable indicative of hypertensive control and its regulation and needs to be controlled by a constrained set of physiological values. Materials and Methods: Sodium nitroprusside is a potent vasoactive drug which is used in the critical care setups to regulate hypertensive emergencies, administered through intravenous route. Many closed-loop drug infusion systems (CL-DIS) powered by fuzzy logic, artificial neural networks, and state-space models have been used to regulate the infusion. In this work, an attempt using proportional resonance controller and fractional-order proportional integral derivative (PID) with a closed loop is modeled and simulated. Results and Discussion: This work proposes a CL-DIS-based proportional resonance controller and fractional-order PID controller, which will respond rationally to the changes in the patient’s condition and activate drug infusion to continue the MAP at the set physiological values of 60 and 70 mmHg. Conclusion: The planned controller setup has potential to be used as a controller for intravenous infusion of drugs and in our work maintained the MAP constrained by set values for the time domain responses for ideal physiological set points.